A sensitive liquid chromatography-tandem mass spectrometry method for the determination of nimbolide in mouse serum: Application to a preclinical pharmacokinetics study - Wang, L.; Khoa Phan, D.; Syn, N.; Xiang, X.; Song, H.; Thuya, W.; Yang, S.; Wong, A.; Kumar, Alan Prem; Yong, W.; Sethi, G.; Ho, P.; et al. (MDPIAG, 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. A sensitive and robust liquid chromatography-tandem mass spectrometric (LC-MS/MS) method was developed and validated for the determination of nimbolide in mouse serum. Exemestane was used as the internal standard (IS). Here, we employed acetonitrile-based protein precipitation (PPT) for serum sample preparation, and performed chromatographic separation using an ODS Hypersil C18 column (100 mm × 2.1 mm, 5 µm) with gradient elution (0.1% formic acid in water vs 100% acetonitrile). The run time was 6 min. Instrumental analysis was performed by electrospray ionization tandem mass spectrometry (ESI-MS/MS) in the multiple-reaction monitoring (MRM) under positive mode. A good linear calibration was achieved in the 5–1000 ng/mL range. The intra-and inter-day precisions for nimbolide were =12.6% and =13.9% respectively. Intra-day accuracy ranged from 96.9–109.3%, while inter-day accuracy ranged from 94.3–110.2%. The matrix effect of nimbolide, detected but consistent at low and high concentrations, do not affect linearity of standard curve. In conclusion, we have developed and validated a sensitive analytical method for determination of a novel natural compound nimbolide in mouse serum, and it has been successfully applied to our preclinical study in investigating the pharmacokinetic properties of nimbolide, which could greatly facilitate the preclinical development of the promising lead compound for anticancer therapy.